A systematic literature review on working capital management – an identification of new avenues. (5th August 2019) - Kayani, Umar Nawaz; De Silva, Tracy-Anne; Gan, Christopher
Abstract : Purpose: This paper aims to provide a review of the existing literature available on working capital (WC) and working capital management (WCM). Design/methodology/approach: A systematic literature review (SLR) methodology is used to review 187 articles selected from referred journals, books and international conferences for the period 1980-2017. Findings: This comprehensive review reveals that much of the focus in the existing literature is paid on investigating the empirical relationship between WCM and firm performance. Furthermore, the attention has been paid towards studying the WC practices. The behavioural aspects, qualitative studies, survey studies and systematic theory development have been ignored in most of the prior studies. These areas have a broader scope for future research. Research limitations/implications: This study is based on literature review and theoretical in nature. Therefore, it does not have any empirical results. Practical implications: So far, a limited literature review studies have been conducted in WCM perspective. This review provides various emerging trends, which may be considered in future research for providing a deep understanding of WCM. Originality/value: This is the first time a detailed review of WCM literature has been conducted by using SLR for the period of 1980-2017. This review will be useful for researchers, business policymaker, finance professionals and all other having direct or indirect concerns with WCM study.